Computer Assisted Radiology / Computergestützte Radiologie CAR ’91 Computer Assisted Radiology - Lemke, Heinz U.; Rhodes, Michael L.; Jaffe, C. C.; Felix, Roland (Springer Berlin Heidelberg, 1991)
CAR is a symposium and exhibition covering the impact of computer and communication systems applied to radiology and other medical disciplines, which use digital imaging for diagnosis and therapy planning. CAR '91 also provides tutorials, but more emphasis is given to a broad variety of specific problems related to medical/technical issues in digital imaging. This is achieved through in-depth presentations of results of current medical imaging projects on a worldwide basis